BIT@FK 2024 (October - November Edition) - Rahmah, Mokhtar; Fauziah, Zainuddin (Faculty of Computing, 2024)
This issue highlights the activities and achievements of our faculty and students. From awards to impactful projects, their successes showcase the energy and talent of our academic community. We are especially proud of our students' accomplishments, whether in competitions or community initiatives. Their dedication reflects the quality of education and guidance from our faculty. This bulletin aims to share knowledge, experiences, and achievements while inspiring growth and learning. We hope you find the articles insightful and motivating. We are committed to maintaining high standards and welcome your feedback to improve future issues. Finally, we thank all contributors, reviewers, and the editorial team for their hard work. We hope you enjoy this issue of the BIT@FK Bulletin.